Nilai-nilai Konseling Islam dalam Junggle Syair Lagu Jam’iyah Shalawat Bhenning - Basriyadi; Mohamat Hadori (Fakultas Dakwah Universitas Ibrahimy, 2022)
Music as a medium at this time is not new, one of the music groups that make a song as a means of delivering moral messages is Jam’iyah Shalawat Bhenning. The songs performed by Jam’iyah Sha- lawat Bhenning contain counseling values, thus, the audience who listens to the lyrics of the song is expected to know and understand the values of Islamic counseling contained in it. One of them is in the Jungle lyric song “Sejukkan heart”. This study aims to determine the values of Islamic counseling contained in the lyrics of the song “Sejukkan Hati”. This research is library research. In this research, the writer collects data by using documentation, collecting lyric text, then analyzing reports to draw conclusions. There are three values of Islamic counseling that are contained in the jungle song “se- juk heart” Jam’iyah Shalawat Bhenning, among others: (1) Messages with sholawat can achieve pe- ace, tranquility, peace of mind and get a lot of sustenance in return. (2) the message of monotheism, the message of the greatness of Allah’s power, and the significance of mentioning and remembering Allah. (3) Instilling a sense of love between others.